Success of Speaking Skills through Presentation Method in Grade 6 Students of SDN Kentong Cepu - Tono, Tono; Wagiran, Wagiran; Dewi Purwati, Panca; Candra Dewi, Dwi Wahyu (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Students' speaking abilities in terms of communication are still minimal in the teaching and learning process. Sixth-grade students at SD Kentong, who are the highest-level students in the school, still exhibit reluctance to speak in front of the class. Some students are still shy when asked to speak and present their work. The aim of this research is to demonstrate the success of students in speaking skills through presentation methods. It aims to train sixth-grade students at SDN Kentong Cepu to confidently present their work in front of others. This study used a descriptive qualitative classroom action research design. The researcher was directly involved in the research process, participating in actions, observing, recording, and documenting events and incidents during the research. The study was conducted in two cycles, namely cycle 1 and cycle 2. Each cycle consisted of four activities: planning, action, observation, and reflection. The results of this study show an improvement in speaking skills, as indicated by the increase in the percentage of students who achieved the minimum completeness criteria (KKM) of 75. In cycle 1, the percentage of completeness from the total number of students (42) was 71.4%, while in cycle 2, it was 95.4%, exceeding the predetermined KKM. This research indicates that the application of presentation methods can improve the success of speaking skills among sixth-grade students at SDN Kentong. Teachers can implement presentation methods in teaching speaking skills to students to enhance their quality, and teachers should have a spirit of enthusiasm, always motivate students, and be creative in creating methods to stimulate students' enthusiasm in learning. Kata kunci: keberhasilan, keterampilan berbicara, metode presentasi